PSYCHOLOGICAL ASPECTS OF COMPLEX MEDICAL AND SOCIAL REHABILITATION OF DISABLED CHILDREN WITH CEREBRAL PALSY - S. A. Nemkova; O. I. Maslova; G. A. Karkashadze; A. M. Mamed'yarov (Педиатрическая фармакология, 2013)
The article deals with psychological aspects of complex medical and social rehabilitation of disabled children with cerebral palsy in detail. Residual-organic cerebral insufficiency at cerebral palsy may be a basis for development of both cognitive disorders and psychogenic reactions, pathological personality formations due to the adverse psychosocial influences caused by disorders of motor and mental functions, which is necessary to take into consideration when conducting rehabilitation measures. The authors considered actual problems of diagnosing and treating the psychological disorders at cerebral palsy and suggested a system of complex mental pathology rehabilitation for this disease, which is aimed at correcting psychoemotional, cognitive and behavioral disorders and also restoring the social adaptation of children and adolescents with cerebral palsy.